The Guideline of the Local Wisdom Herbal Tea Product Development for Promote Creative Economy in Kanchanaburi Province - Daoruang et al., Runchida (Journal of Management Science Nakhon Pathom Rajabhat University, 2023)
This research aims to study sought to investigate the basic information, operation, problem conditions, product development needs, and guidelines for the development of herbal tea products from local wisdom to promote the creative economy inKanchanaburi. The data collection for this research will involve two groups of participants. The main data providers were community enterprises that produce herbal tea products based on local wisdom in Kanchanaburi province. The sampling method for this group will be a convenience sampling technique, with a minimum of five groups of 10 individuals. Another one is the sample groups consisting of individuals who have previously purchased herbal tea products in Kanchanaburi province. The sampling method for this group will be a convenience sampling technique, with a sample size of 400 people. The qualitative research findings from the interviews with community enterprises that produce herbal tea products based on local wisdom in Kanchanaburi province, turmeric, ginger, lemongrass, pandan leaves, citronella, and butterfly pea are the main herbs grown. Their business is wholesale and middleman. Storage of fungal diseases and water constraints cause production fluctuations in the communities. Moreover, community groups want to pass down local knowledge. Thus, they have attempted to create a learning center for herbal medicine students. They also strive to match commercial shop product quality. The quantitative research results from individuals who have previously purchased herbal tea products in Kanchanaburi province aimed to identify strategies for product development. It was found that the variations in demographic factors significantly influenced purchase decisions for different product options. Additionally, factors related to purchasing behavior, such as the reasons for selecting a particular product, the location of the point of sale, and the motivations behind purchasing from specific sources, also influenced diverse purchasing decisions. The change in purchasing decisions was 45.20%, with the remaining 54.80% impacted by other variables. When each side is considered, products have the most influence on the purchase decision (Beta = 0.31), followed by price (Beta = 0.26), place (Beta = 0.18), and promotion (Beta = 0.10). Therefore, the development of herbal tea products should focus on packaging that preserves product quality. The products should be diverse to cater to the needs of various consumer groups, and clear product information should be provided to instill confidence in consumers. Article history: Received 24 March 2023 Revised 11 June 2023 Accepted 12 June 2023 SIMILARITY INDEX = 3.83 %